ANALISA TERHADAP PERJANJIAN JUAL BELI TANAH DI BAWAH TANGAN PADA PUTUSAN MAHKAMAH AGUNG NOMOR : 152/Pdt.G/2021/PN Bks - Putri Kinanti; Rafi Rangga Saputra; Chris Matthew Tobing; Indah Kusuma Wardani; Muhammad Abdul Aziz Hasibuan; Alya Rahmawati; Mauladiana Qibtiya; Melisa Nurjaya; Wardani Rizkianti (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
A private land sale and purchase agreement is a written contract between two parties without the involvement of an authorized public official. Although legally, a private land sale and purchase agreement meets the requirements set out in Article 1320 of the Indonesian Civil Code, which governs the legal validity of contracts, such an agreement carries significant consequences in terms of proof and may be subject to challenges regarding its validity. This study aims to examine, analyze, and address the validity of private land sale and purchase agreements under the provisions of named contracts as regulated in the Indonesian Civil Code, the legal protection afforded to the parties involved in such agreements, and the evidentiary mechanisms for resolving disputes arising from private land sale and purchase transactions. The findings of this research reveal that, while the sale is substantively valid, in terms of agrarian legal formalities, a private land sale and purchase agreement is not considered fully complete, as it is not executed through a Land Deed Official (PPAT) deed. Therefore, to protect the parties involved in a private land sale and purchase agreement, it is essential to strengthen the agreement through proper legal authorization.